Mycobacterial extracellular vesicles and host pathogen interactions. Issue 4 (6th April 2018) - Gupta, Shamba; Rodriguez, G Marcela
Abstract: Mycobacteria, like other bacteria, archaea and eukaryotic cells, naturally release extracellular vesicles (EVs) to interact with their environment. EVs produced by pathogenic bacteria are involved in many activities including cell–cell communication, immunomodulation, virulence and cell survival. Although EVs released by thick cell wall microorganisms like mycobacteria were recognized only recently, studies of Mycobacterium tuberculosis EVs already point to their important roles in host pathogen interactions, opening exciting new areas of investigation. This minireview will summarize the current understanding of mycobacterial EV biology and roles in pathogenesis and will discuss their potential therapeutic applications. Abstract : Mycobacterium tuberculosis releases membrane vesicles into the environment; these vesicles contain a broad range of microbial factors important for virulence and molecules that alter host defense systems.